Influence of Airfoil Structure on Performance ofVertical Open Refrigerated Display Cabinet - Yuan Pei; Zeng Qinghui; Lei Zhenglin; Wu Yixiao; Yanli; Zhang Enhua; Hu Chaolong; Zhou Kai (Zhileng xuebao)
In this study, an airfoil structure was added in front of the display cabinet shelf to optimize the performance of a vertical open-type refrigerated display cabinet. The influence of the airfoil structure on the performance of a vertical open refrigerated display cabinet was studied by testing the performance of the refrigerated display cabinet after addition of the airfoil structure. The test results show that under an ambient temperature of 25 ℃and relative humidity of 60 %, the evaporation temperature of the refrigeration system increased from ?6.3 ℃ to ?4.5 ℃ after installation of the airfoil structure. The average temperature fluctuation of supply and return air varied from 0.6?4.4 ℃, 10.3?12.0 ℃ to 1.8?3.0 ℃ and 6.0?7.4 ℃. The supply air velocity was essentially the same, and the return air velocity decreased by 10.2%–16.9%. The thermal permeability coefficient in the display cases decreased by 46%–48%. The maximum average temperature difference of food in different layers of the cabinet decreased by 31%, and the maximum average temperature difference of food inside and outside decreased by 46.2%. The total heat emission of the showcase decreased from 82.33 kW?h/24 h to 66.49 kW?h/24 h. The total energy consumption of the system decreased from 42.91 kW?h/24 h to 33.61 kW?h/24 h. The results show that the refrigerating system performance, air curtain performance, temperature uniformity, and energy utilization ratio of the open display cabinet can be improved by adding an airfoil structure at the front end of the shelf.